2003
DOI: 10.1302/0301-620x.85b7.13930
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic measurement of joint space height in non-osteoarthritic tibiofemoral joints

Abstract: There have been many reports which suggest that in patients with tibiofemoral osteoarthritis, a reduction in joint space is demonstrated better on weight-bearing radiographs taken with the knee in semiflexion than in full extension. The reduction has been attributed to the loss of articular cartilage in the contact area in a semiflexed arthritic knee. None of these studies have, however, included normal knees. We have therefore undertaken a prospective, double-blind, randomised study in order to evaluate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Variability in MJSW was also seen in the case of knees with no radiographic OA, where the MJSW was 0.6 mm lower on average in the FFV than in SEV. In this respect, our results agree with those of an earlier study and point to natural variability in MJSW possibly caused (at least in part) by variations in the thickness of the articular cartilage between different parts of the knee and sliding of the knee joint during flexion (Deep et al 2003, Patel et al 2004). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Variability in MJSW was also seen in the case of knees with no radiographic OA, where the MJSW was 0.6 mm lower on average in the FFV than in SEV. In this respect, our results agree with those of an earlier study and point to natural variability in MJSW possibly caused (at least in part) by variations in the thickness of the articular cartilage between different parts of the knee and sliding of the knee joint during flexion (Deep et al 2003, Patel et al 2004). …”
Section: Discussionsupporting
confidence: 92%
“…However, it has been reported that narrowing of the joint space is better visualized in fixed flexion views (FFVs), which have also been found to be reproducible and easy to use in clinical practice (Piperno et al 1998, Vignon et al 2003, Duddy et al 2004). However, one report has claimed that narrowing of the joint space width in flexed knee radiographs is not always caused by OA (Deep et al 2003) and there is still disparity regarding the optimal knee flexion angle (Bhatnagar et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the flexion position is considered more useful than the extension position when evaluating the joint space by plain radiography because the meniscus interferes with and the tibial posterior tilt influences the evaluation18,1214). During conventional acquisition, images are acquired in a standing position, with the knee set at a flexion angle of 20°–45° using a goniometer, but it may be difficult for elderly individuals and patients with marked arthralgia to retain this posture1,2,8,12,13,15). In acquiring FFV images, the anterior thigh is placed in close contact with the cassette and the tips of the toes are placed in the same plane as that of the cassette, thus fixing the knee flexion angle according to the physique of each patient6).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that there may be a difference of up to 2 mm in the two views. This could be attributed to inherent differential thickness of articular cartilage and change in areas of contact between femoral and tibial condyles [16].…”
Section: Discussionmentioning
confidence: 99%